IL-1β Induced Cytokine Expression by Spinal Astrocytes Can Play a Role in the Maintenance of Chronic Inflammatory Pain - Gajtkó, Andrea; Bakk, Erzsébet; Hegedűs, Krisztina; Ducza, László; Holló, Krisztina (Frontiers in Physiology, 2020)
It is now widely accepted that the glial cells of the central nervous system (CNS) are key players in many processes, especially when they are activated via neuron-glia or glia-glia interactions. In turn, many of the glia-derived pro-inflammatory cytokines contribute to central sensitization during inflammation or nerve injury-evoked pathological pain conditions. The prototype of pro-inflammatory cytokines is interleukin-1beta (IL-1β) which has widespread functions in inflammatory processes. Our earlier findings showed that in the spinal cord (besides neurons) astrocytes express the ligand binding interleukin-1 receptor type 1 (IL-1R1) subunit of the IL-1 receptor in the spinal dorsal horn in the chronic phase of inflammatory pain. Interestingly, spinal astrocytes are also the main source of the IL-1β itself which in turn acts on its neuronal and astrocytic IL-1R1 leading to cell-type specific responses. In the initial experiments we measured the IL-1β concentration in the spinal cord of C57BL/6 mice during the course of complete Freund adjuvant (CFA)-induced inflammatory pain and observed a peak of IL-1β level at the time of highest mechanical sensitivity. In order to further study astrocytic activation, primary astrocyte cultures from spinal cords of C57BL/6 wild type and IL-1R1 deficient mice were exposed to IL-1β in concentrations corresponding to the spinal levels in the CFA-induced pain model. By using cytokine array method we observed significant increase in the expressional level of three cytokines: interleukin-6 (IL-6), granulocyte-macrophage colony stimulating factor (GM-CSF) and chemokine (C-C motif) ligand 5 (CCL5 or RANTES). We also observed that the secretion of the three cytokines is mediated by the NFkB signaling pathway. Our data completes the picture of the IL-1β-triggered cytokine cascade in spinal astrocytes, which may lead to enhanced activation of the local cells (neurons and glia as well) and can lead to the prolonged maintenance of chronic pain. All these cytokines and the NFkB pathway can be possible targets of pain therapy.